Factors affecting Malaysian university students’ purchase intention in social networking sites - Fard, Saeideh Sharifi; Tamam, Ezhar; Hassan, Md Salleh; Waheed, Moniza; Zaremohzzabieh, Zeinab (Cogent OA, 2016)
This study applied the unified theory of acceptance and use of technology 2 to examine acceptance and use of social networking sites in a marketing setting. This study uses 370 regular higher education students in Malaysia as respondents. Quantitative method is used. The findings revealed that performance expectancy (PE) and hedonic motivation were the main factors that influence users’ online purchase intention (PI) through social networking sites (SNSs) in Malaysia. As for moderating influences of gender and age, the results showed that gender significantly moderated purposed association between these four elements and the online PI, while the moderating effect of age was only recognized in PE. Findings of this research offer practitioners with better insights that would aid them in developing effective online marketing strategies to attract online purchasing users through SNSs.